Applications of within-stimulus errorless learning methods for teaching discrimination skills to individuals with intellectual and developmental disabilities: A systematic review. (February 2020) - Markham, Victoria A.; Giles, Aimee F.; Roderique-Davies, Gareth; Adshead, Victoria; Tamiaki, Georgia; May, Richard J.
Abstract: Errorless learning is an instructional strategy used widely with individuals with intellectual and developmental disabilities. The present systematic review aims to update the literature on the application of 'within-stimulus' errorless procedures. The protocol was registered with PROSPERO (CRD42018118385). Twenty-eight articles including 283 participants met the operationally defined inclusion criteria. In the majority of cases, the errorless learning procedures evaluated led to improvements in acquiring discrimination skills. Most of the reviewed studies evaluated stimulus fading. Results are discussed in relation to the selection of within-stimulus procedures. Areas identified for future research include further evaluations of other within-stimulus tactics, as well as further refinement of procedural parameters.